Pelatihan Kewirausahaan Keterampilan Menjahit Bagi Ibu-Ibu PKK - Ismuhadi; Silaturrahmi; Hasanah, Uliatun (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
This training aims to empower the community, it is hoped that from this training the community is independent in the financial sector. The research method used is qualitative with a descriptive approach that is library research, obtained from reading literature from related books, journals, articles/news reports and also by analyzing field observation data and documentation, both pictures and documents that provide information related to the training.  The results, it was found that the woman were very enthusiastic in the training activities, the first being taught by the sewing tutor was basic knowledge about sewing, measuring, how to make and drawing patterns so how to sew. This benefit is for women as independent individuals, and able to provide financial security to their family members. at least to meet household needs this training will provide a great opportunity to help the family and community economy. The training does not run well without the cost of training, the cost of factors that support the training well and smoothly. Existing as a village in community empowerment, funds obtained for training from village funds and even training are in a program from village funds in empowering communities this is an example for other villages in dealing with insufficient funds.